2012
DOI: 10.1161/atvbaha.112.252098
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Reduces Myocardial Injury Undergoing Noncoronary Artery Cardiac Surgery

Abstract: Objective— Myocardial injury during cardiac surgery is a major cause of perioperative morbidity and mortality. We determined whether perioperative statin therapy is cardioprotective in patients undergoing noncoronary artery cardiac surgery and the potential mechanisms. Methods and Results— One hundred fifty-one patients undergoing noncoronary artery cardiac surgery were randomly assigned to either a statin group (n=77) or a control group (n=74). Simvast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…To stimulate NO release, VEGF (50 ng/ml) was added to all plates. And then the supernatant was used to determine NO generation by Griess assay (Nanjing Jiancheng Bioengineering Institute, Nanjing, China), and the cellular proteins were harvested for concentration determination by a bicinchoninic acid protein assay (Merck, Whitehouse Station, NJ), as described previously (2,26).…”
Section: Methodsmentioning
confidence: 99%
“…To stimulate NO release, VEGF (50 ng/ml) was added to all plates. And then the supernatant was used to determine NO generation by Griess assay (Nanjing Jiancheng Bioengineering Institute, Nanjing, China), and the cellular proteins were harvested for concentration determination by a bicinchoninic acid protein assay (Merck, Whitehouse Station, NJ), as described previously (2,26).…”
Section: Methodsmentioning
confidence: 99%
“…However, these recommendations are based on randomized trials that were small and had other important limitations. An updated meta-analysis of the results from previously published randomized trials of perioperative statin therapy (15)(16)(17)(18) showed an approximate halving of the incidence of postoperative AF with statins as compared with placebo. However, those trials involved small numbers of patients and had other important limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent systematic Cochrane review of those trials showed evidence of selective reporting and publication bias (31). The suggestion that perioperative statin therapy might be associated with less severe myocardial damage derives from one randomized, placebocontrolled trial involving 200 patients undergoing CABG surgery (32) and from a non-blinded randomized trial involving 151 patients undergoing non-coronary cardiac surgery, which also reported improved left ventricular function (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins can mobilize bone marrow endothelial stem cells and promote recovery from nerve injury. Mobilization of autologous BMSCs has improved treatment of ischemic cerebrovascular diseases to a certain extent (Almansob et al, 2012;Uhiara et al, 2012). Vasculogenesis and neurogenesis are two major pathophysiologic processes that occur in the brain after cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%